2000
DOI: 10.1359/jbmr.2000.15.6.1056
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Ossification of Degenerating Rat Skeletal Muscle Induced by Adenovirus-Mediated Transfer of Bone Morphogenetic Protein-2 Gene

Abstract: In vivo gene transfer is a recently developed device for efficient delivery of a therapeutic recombinant protein.We formulated the hypothesis that a high level of expression of bone morphogenetic protein 2 (BMP-2) could be a future therapeutic modality in terms of inducing substantial bone formation in vivo. First, to test this hypothesis, adenoviruses carrying BMP-2 gene were directly injected into the soleus muscle of adult rat. The BMP-2 gene was successfully overexpressed in the target muscle by adenovirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…With rare exception, heterotopic bone is found below the neurological level of injury [26]. In traumatic SCI, as well as other traumatic conditions, the two primary factors that appear responsible for the etiology of bone deposition at a cellular and molecular level appear to be the presence of BMPs [29][30][31][32] and the ischemic degeneration of involved muscle [33][34]. The sources of BMPs in muscle are mesenchymal cells and endothelial cells; the target cells in the muscle that BMPs act upon are mesenchymal stem cells and smooth muscle cells [35].…”
Section: Proposed Mechanisms Of Heterotopic Ossification Formationmentioning
confidence: 99%
“…With rare exception, heterotopic bone is found below the neurological level of injury [26]. In traumatic SCI, as well as other traumatic conditions, the two primary factors that appear responsible for the etiology of bone deposition at a cellular and molecular level appear to be the presence of BMPs [29][30][31][32] and the ischemic degeneration of involved muscle [33][34]. The sources of BMPs in muscle are mesenchymal cells and endothelial cells; the target cells in the muscle that BMPs act upon are mesenchymal stem cells and smooth muscle cells [35].…”
Section: Proposed Mechanisms Of Heterotopic Ossification Formationmentioning
confidence: 99%
“…Although there are several studies which have shown evidence for skeletal regeneration in vivo using ex vivo modified stromal cells, myoblasts, or fibroblasts, 10,15,16,22,24,25 our study is unique in that it provides quantitative data on the extent of healing by valid bone density measurements. Furthermore, our data demonstrate that the healing of a critical calvarial defect is dependent on the time of exposure, as well as the number of BMP4-expressing stromal cells implanted.…”
Section: Bmp4-producing Cells Were Identified By Immunostaining (Browmentioning
confidence: 99%
“…[9][10][11][12][13][14] Accordingly, it has been shown that adenoviral transfer of BMP2 can stimulate bone formation at ectopic sites 16 and promote healing of a segmental defect in long bones. 9,14 In as much as the results of previous work using adenoviral vectors are promising and adenoviral vector systems have the advantage of high levels of gene expression acutely, adenoviral vector systems also have two important disadvantages: (1) these vectors, even with the use of 'gutted' adenoviral vectors, frequently elicit strong immune response, which is highly undesirable.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, direct injection of adenoviral vector encoding BMP-2 induces little bone formation in immunocompetent animals and may cause substantial inflammation at the injection site [9,21].…”
Section: Introductionmentioning
confidence: 99%